Nucleoporin-Regulated MAP Kinase Signaling in Immunity to a Necrotrophic Fungal Pathogen. Issue 2 (2nd September 2016) - Genenncher, Bianca; Wirthmueller, Lennart; Roth, Charlotte; Klenke, Melanie; Ma, Liang; Sharon, Amir; Wiermer, Marcel
Abstract : Arabidopsis nuclear pore complex protein Nup88/MOS7 interacts with Nup98a/b and promotes nuclear accumulation of MPK3 to mount a robust immune response against the necrotrophic fungus Botrytis cinerea. Abstract: Pathogen-responsive mitogen-activated protein kinase (MAPK or MPK) cascades relay signals from activated immune receptors across the nuclear envelope to intranuclear targets. However, in plants, little is known about the spatial control of MAPK signaling. Here, we report that the Arabidopsis ( Arabidopsis thaliana ) nuclear pore complex protein Nup88/MOS7 is essential for immunity to the necrotrophic fungus Botrytis cinerea . The mos7-1 mutation, causing a four-amino acid deletion, compromises B. cinerea -induced activation of the key immunoregulatory MAPKs MPK3/MPK6 and reduces MPK3 protein levels posttranscriptionally. Furthermore, MOS7 contributes to retaining a sufficient MPK3 abundance in the nucleus, which is required for full immunity to B. cinerea . Finally, we present a structural model of MOS7 and show that the mos7-1 mutation compromises interactions with Nup98a/b, two phenylalanine-glycine repeat nucleoporins implicated in maintaining the selective nuclear pore complex permeability barrier. Together, our analysis uncovered MOS7 and Nup98 as novel components of plant immunity toward a necrotrophic pathogen and provides mechanistic insights into how these nucleoporins coordinate nucleocytoplasmic transport to mount a robust immune response.